Askin Tumour on Tc-99m MDP Bone Scan - Mariyam Waseem,; Fatima Yousaf,; Aamna Hassan,; Ahmad Quraishy, (Journal of the Pakistan Medical Association, 2025)
Askin tumour is a rare primitive neuroectodermal tumour of the chest wall belonging to Ewing family of tumours. It is diagnosed on histopathology and imaged with CT and MRI. Typical symptoms include pain, dyspnoea and weight loss. Generally has an aggressive course and is often misdiagnosed as other blue cell tumours. Standard treatment is multidisciplinary; combining chemotherapy with surgery and/or radiotherapy. Here we present a few cases of Askin tumour imaging seen on Tc-99m MDP bone scan. Keywords: Askin tumour, Ewing Sarcoma, Tc-99m MDP bone scan